LATAR BELAKANG FILOSOFIS DAN SOSIOLOGIS INTEGRASI AGAMA DAN SAINS - Harahap, Adek Saputra; Amril M, Amril M; Dewi, Eva; pengelola, pengelola (LPPM STAI Ihyaul Ulum Gresik, 2025)
This research describes the backgroundPhilosophical, Sociological Integration of Religion and Science. The aim of this research is tounderstand aboutbackgroundPhilosophical, Sociological Integration of Religion and Science,.The study method used is literature study or library research by collecting various information from related journals/literaturebackgroundPhilosophical, Sociological Integration of Religion and Science.Data collection with the results of previous research which supports the data in this research.The result is The philosophical aspect is one way of expressing the wisdom that lies behind the teachings of the Islamic religion, for example, Islamic teachings teach to carry out congregational prayers with the aim, among other things, that a person can experience the wisdom of living side by side with other people, and so on. As for the sociological aspect, there are many religious teachings related to social problems. The great attention of religion to social problems further encourages religious people to understand social sciences as a tool for understanding their religion.